Ammonium NHC-tagged olefin metathesis catalysts – influence of counter-ions on catalytic activity. (23rd April 2018) - Tracz, Andrzej; Gawin, Anna; Bieniek, Michał; Olszewski, Tomasz K.; Skowerski, Krzysztof
Abstract : Ruthenium-based catalysts bearing quaternary ammonium groups in their N-heterocyclic carbene (NHC) fragments and different counter-ions were synthesised and tested in various olefin metathesis transformations. Abstract : Ruthenium-based catalysts bearing quaternary ammonium groups in their N-heterocyclic carbene (NHC) fragments and different counter-ions were synthesised and tested in various olefin metathesis transformations. Differences in catalytic activity in correlation with the nature of the present counter-ion were revealed. The unique properties of the described catalysts allow for the effective preparation of a variety of metathesis products with low ruthenium contamination and under green chemistry conditions.